Sesquiterpenes rich essential oil from Garcinia celebica L. and its cytotoxic and antimicrobial activities. Issue 23 (1st December 2020) - Tan, Wen-Nee; Tan, Zi-Hui; Zulkifli, Nurul Izzati; Nik Mohamed Kamal, Nik Nur Syazni; Rozman, Nur Amiera Syuhada; Tong, Woei-Yenn; Leong, Chean-Ring; Lim, Jun-Wei
Abstract: Garcinia celebica L., locally known as " manggis hutan " in Malaysia is widely used in folkloric medicine to treat various diseases. The present study was aimed to examine the chemical composition of the essential oil from the leaves of G. celebica L. (EO-GC) and its cytotoxic and antimicrobial potential. EO-GC obtained by hydrodistillation was analysed using capillary GC and GC-MS. Twenty-two compounds were identified, dominated by α -copaene (61.25%), germacrene D (6.72%) and β -caryophyllene (5.85%). In the in vitro MTT assay, EO-GC exhibited significant anti-proliferative effects towards MCF-7 human breast cancer cells with IC50 value of 45.2 μg/mL. Regarding the antimicrobial activity, it showed better inhibitory effects on Gram-positive bacteria than Gram-negative bacteria and none on the fungi and yeasts tested. Graphical Abstract: